파킨슨병의 건강검진 및 일상 모니터링, 관리 기술의 특허 동향 분석 - 김근호; 서정우; 김지원; Kim, Keun Ho; Seo, Jeong Woo; Kim, Ji Won (대한한방내과학회지, 2020)
Objectives: Parkinson's disease (PD) is a neurodegenerative disease of the elderly characterized by impaired behavior from lack of dopamine secretion. However, no accurate quantitative diagnosis method has been established. The purpose of this study was to analyze the patent trends (PTs) of health examination and daily monitoring/healthcare technology for PD. Methods: For analyzing PTs, a search summary for classifying each analysis target technology was set, and a final search formula was constructed by collecting keywords. After constructing a database of related patents through the final search formula, noise was removed to extract valid patents. PTs by major countries were analyzed using the valid patents, and PTs and growth stages were analyzed by the detailed technologies. Results: The survey analysis showed that, despite the existence of unpublished patents between 2018 and 2020, patent activity has increased rapidly in the recent period, and this increasing trend was led by the USA. This technology is considered to be in its early- or mid-stage growth period, which means that the marketability is high and the barriers are low. Korea's market share is only about 25%, but it has a larger number of applications than those of Europe and Japan. Integrated monitoring and diagnosis technologies for PD have a share of 34%. Conclusion: The advances in diagnosis and healthcare technology for PD means that traditional Korean medicine must continue to pay attention to related technologies and to review plans that are applicable to clinical practice.